Effect of Hub-Ratio on Performance of Asymmetric Dual-Rotor Small Axial Fan - Wu, Yongmin; Jin, Yingzi; Jin, Yuzen; Wang, Yanping; Zhang, Li (Scientific Research, 2013)
Currently, domestic and abroad scholars put more attention on contra-rotating dual-rotor axial fan. But there is less scholars study on asymmetric dual-rotor small axial fan, which is one of the contra-rotating dual-rotor axial fans. Like axial fan, many factors have influence on the performance of the asymmetric dual-rotor small axial flow fan, such as the wheel hub ratio, blade shape, blade number, stagger angle and the tip clearance. Because wheel hub ratio has great impact on the performance of the fan, we choose the size of wheel hub ratio as a variable factor to study the model change. There is a different wheel hub ratio between front stage impeller and rear stage of asymmetric dual-rotor small axial fan, so it is very beneficial to select the greater wind area that the fan area of external diameter minuses the area occupied by the blades and the hub as front stage impeller. In this paper, the hub-ratio of front stage impeller is 0.72, and that of rear stage is 0.72, 0.67 and 0.62 respectively along with the front stage impeller. Three kinds of models with different hub ratio of rear stage are simulated using the CFD software and the static characteristics are obtained. Based on the experimental test results, the internal flow field of the asymmetric dual-rotor small axial fan is analyzed in detail, the impact trends of different hub-ratio on the performance of asymmetric dual-rotor small axial fan are obtained and the argument of structure optimization for dual-rotor small axial fan is provided.
Keywords: Asymmetric Dual-Rotor; Axial Flow Fan; Hub Ratio; Numerical Simulation; Internal Flow Field